MULTICRITERIA SELECTION OF THE OPTIMAL DESIGN OPTIONS OF TELECOMMUNICATION FACILITIES - Bezruk, Valeriy; Chebotareva, Daria; Skoryk, Yulia (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2018)
The peculiarities of the application of methods of multicriteria optimization in the choice of optimal design options of telecommunication facilities taking into account a set of quality indicators are considered. Examples of multicriteria analysis and the choice of optimal variants for various telecommunication facilities, in particular, the variants of radio network construction of a mobile communication system, the structure and methods of routing in multiservice networks, ad-hoc networks, sensor and actuator networks, as well as mobile communication technologies of the 4th generation are provided.